Dielectrophoresis‐Assisted Integration of 1024 Carbon Nanotube Sensors into a CMOS Microsystem. Issue 17 (15th March 2017) - Seichepine, Florent; Rothe, Jörg; Dudina, Alexandra; Hierlemann, Andreas; Frey, Urs
Abstract : Carbon‐nanotube (CNT)‐based sensors offer the potential to detect single‐molecule events and picomolar analyte concentrations. An important step toward applications of such nanosensors is their integration in large arrays. The availability of large arrays would enable multiplexed and parallel sensing, and the simultaneously obtained sensor signals would facilitate statistical analysis. A reliable method to fabricate an array of 1024 CNT‐based sensors on a fully processed complementary‐metal‐oxide‐semiconductor microsystem is presented. A high‐yield process for the deposition of CNTs from a suspension by means of liquid‐coupled floating‐electrode dielectrophoresis (DEP), which yielded 80% of the sensor devices featuring between one and five CNTs, is developed. The mechanism of floating‐electrode DEP on full arrays and individual devices to understand its self‐limiting behavior is studied. The resistance distributions across the array of CNT devices with respect to different DEP parameters are characterized. The CNT devices are then operated as liquid‐gated CNT field‐effect‐transistors (LG‐CNTFET) in liquid environment. Current dependency to the gate voltage of up to two orders of magnitude is recorded. Finally, the sensors are validated by studying the pH dependency of the LG‐CNTFET conductance and it is demonstrated that 73% of the CNT sensors of a given microsystem show a resistance decrease upon increasing the pH value. Abstract : A complementary‐metal‐oxide‐semiconductor microsystem with 1024 carbon nanotube sensors is fabricated using a floating‐electrode dielectrophoresis technique. The process is optimized for a high yield of functional sensors formed by a controlled low number of carbon nanotubes. Characterization results of the resulting devices are presented. The sensor array is validated by studying the pH dependency in a liquid‐gate field‐effect transistor configuration.